Pengaruh Kualitas Produk Dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Pada Layanan Indihome Di PT. Telkom Akses Regional Operation Center 2 - Herni Herinda Syalawati; Bertadi Nurseno (JAMBIS : Jurnal Administrasi Bisnis, 2025)
Abstract.This research aims to determine the effect of product quality and service quality on customer satisfaction.This research uses associative quantitative data with the population of this research, namely IndiHomecustomers in region 2 which includes the Banten, Bekasi, Bogor, West Jakarta, Central Jakarta, SouthJakarta, East Jakarta, North Jakarta and Tangerang areas. The sampling technique in this study usednonprobability sampling using accidental sampling technique, so that the number of respondents was100 respondents. This research method uses multiple linear regression with the SPSS applicationversion 29.0.2.0 (20). The results of this research show that product quality has a positive and significanteffect on customer satisfaction, service quality has a positive and significant effect on customersatisfaction. Overall, product quality and service quality have a positive and significant effect on customersatisfaction. Keywords: Product Quality, Service Quality, Customer Satisfaction